Teaching Character Development Through Movie Analysis: A Case Study Of Setting And Psychology In The Hunger Games: The Ballad Of Songbirds And Snakes - Pidada, Ida Ayu Nadyaswari Putri; Parthama, I Gusti Ngurah (Peneliti.net, 2025)
This study examines how setting influences the psychological development of the main character in the movie The Hunger Games: The Ballad of Songbirds and Snakes and explores its pedagogical relevance in literature and character education. Using William Kenney's theory of setting and Elizabeth Hurlock's theory of character development, the study analyzes the transformation of Coriolanus Snow as a result of his social environment. The findings highlight how literary and cinematic analysis can be applied in classroom settings to teach students about the interplay between environment and psychological growth. This article offers educators a model for using narrative texts to foster deeper understanding of character development and moral complexity.